Three moments of love in Leonard Cohen and Bruce Cockburn - Nonnekes, Paul (Black Rose Press, 2001)
"Three Moments of Love is a series of reflections on the work of Leonard Cohen and Bruce Cockburn. These two artists, so different in style and temperament, are brought together in one work in order to compare and examine the way in which they approach the question of love and desire: in their art and in their life."